COMPARING RIPASA SCORE AND ALVARADO SCORE IN AN ACCURATE DIAGNOSIS OF ACUTE APPENDICITIS - Noor, Shehryar; Wahab, Abdul; Afridi, Gulsharif; Ullah, Kaleem (Journal of Ayub Medical College Abbottabad, 2020)
Background: The clinical diagnosis of acute appendicitis remains difficult despite the use of different scoring systems. A high rate of negative appendectomies is no longer acceptable. This study was aimed to compare RIPASA score and Alvarado score in Pakistani population for the diagnosis of acute appendicitis using histopathology as a gold standard. Methods: This cross-sectional prospective study was carried out from January to September 2018 in the Accident and Emergency Department and Department of Surgery, Khyber Teaching Hospital, Peshawar. Patients clinically suspected as acute appendicitis aided by routine ultrasound were included in the study. RIPASA and Alvarado scoring was done in all patients. After appendectomies, specimen was sent for histopathological examination. A score of 7.5 was considered as optimal cutoff threshold for RIPASA and 7 for Alvarado score. Sensitivity, Specificity, Positive Predictive Value (PPV), Negative Predictive Value (NPV) and accuracies of both scores were calculated. Results: A total of 300 patients were included in the study. The mean age of patients was 28±10.0 years and there were 176 males. Sensitivity, Specificity of RIPASA score and Alvarado score was found to be 98.52% and 90%, and 68.15% and 80% respectively. Positive Predictive Value and NPV of RIPASA score was 98.88% and 97.67% as compared to 96.84% and 21.82% for Alvarado score. Diagnostic accuracy of RIPASA and Alvarado score was 97.67% and 69.33% respectively. Conclusion: RIPASA scoring system is a more accurate, sensitive and specific indicator of diagnosing acute appendicitis as compared to Alvarado scoring system Keywords: RIPASA; Alvarado; Acute Appendicitis